Allosteric modulation of nicotinic and GABAA receptor subtypes differentially modify autism-like behaviors in the BTBR mouse model. (November 2017) - Yoshimura, Ryan F.; Tran, Minhtam B.; Hogenkamp, Derk J.; Ayala, Narielle L.; Johnstone, Timothy; Dunnigan, Andrew J.; Gee, Timothy K.; Gee, Kelvin W.
Abstract: Autism spectrum disorder (ASD) is associated with two core symptoms (social communication deficits and stereotyped repetitive behaviors) in addition to a number of comorbidities. There are no FDA-approved drugs for the core symptoms and the changes that underlie these behaviors are not fully understood. One hypothesis is an imbalance of the excitation (E)/inhibition (I) ratio with excessive E and diminished I occurring in specific neuronal circuits. Data suggests that both gamma-aminobutyric acidA (GABAA ) and α7 nicotinic acetylcholine receptors (nAChRs) significantly impact E/I. BTBR T + tf /J (BTBR) mice are a model that display an autism-like phenotype with impaired social interaction and stereotyped behavior. A β2/3-subunit containing GABAA receptor (GABAA R) subtype selective positive allosteric modulator (PAM), 2–261, and an α7 nAChR subtype selective PAM, AVL-3288, were tested in social approach and repetitive self-grooming paradigms. 2–261 was active in the social approach but not the self-grooming paradigm, whereas AVL-3288 was active in both. Neither compound impaired locomotor activity. Modulating α7 nAChRs alone may be sufficient to correct these behavioral and cognitive deficits. GABAergic and nicotinic compounds are already in various stages of clinical testing for treatment of the core symptoms and comorbidities associated with ASD. Our findings and those of others suggest that compounds that have selective activities at GABAA R subtypes and the α7 nAChR may address not only the core symptoms, but many of the associated comorbidities as well and warrant further investigation in other models of ASD. Highlights: GABAA R subtype selective PAMs ameliorate aberrant social but not repetitive behaviors. α7 nAChR PAMs ameliorate both social and repetitive behaviors. GABAA R and nAChR PAMs may address the core symptoms and comorbidities of autism.